TEACHING VOCABULARY USING FLASHCARDS AND WORD LIST - Elsa Yusrika Sitompul (Journal of English and Education, 2013)
The study was conducted to investigate the effect of using flashcards or word list on fifty graders’ vocabulary mastery and to discover the students’ responses toward both strategies in learning English vocabulary. This study employed a quasi-experimental research design which involved two classes, grouped into experimental and control groups with a relatively similar vocabulary mastery before treatment. The experimental group received flashcards treatment while the control group received word list treatment. The results showed that students’ vocabulary mastery improved after they were taught by using flashcards and wordlist. The students in experimental group admitted that they could memorize the words easily, be more motivated to learn English and understand vocabulary easily. On the other hand, students in the control group perceived that word list was a tedious strategy. Hence, it was concluded that flashcards is recommended to teach vocabulary to young learners.  Keywords:Vocabulary, vocabulary learning, flashcards, word list, teaching strategy